Parents' constructions of normality and pathology in child mental health assessments. Issue 3 (28th November 2019) - O'Reilly, Michelle; Muskett, Tom; Karim, Khalid; Lester, Jessica N.
Abstract: Central to a contemporary understanding of childhood is the developmental and clinical‐medical construct of the 'normal' child. When judged to fall outside of culturally, socially and historically situated parameters of 'normality', children become labelled as 'deviant from the norm'; for instance, in mental health contexts where this may provide the basis for psychiatric diagnosis. However, judgements of a child's 'normality' are further complicated by the range of individuals who may have a stake in that construction, including parents/carers, professionals and the child themselves. Using discursive psychology, we analysed 28 video‐recorded UK child mental health assessments, to examine ways that parents presented concerns about their children's development. They did this by drawing on notions of 'ab/normal', in ways that functioned to legitimise their need for services and built a rhetorical case to demonstrate clinical need; often by contrasting the child with other 'typical' children and/or contrasting the same child's behaviour in different settings or contexts. We concluded that given the growing crisis in child mental health, initial assessments play a crucial clinical role in determining diagnosis and labelling, and therefore, a critical discussion of these concepts and processes is essential.